Pengaruh Motivasi, Pengetahuan, Dan Kemajuan Teknologi Terhadap Keputusan Berinvestasi Mahasiswa UIN Sumatera Utara Di Pasar Modal Syariah - Endah Hardiati; Annio Indah Lestari Nasution; Muhammad Lathief Ilhamy Nasution (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the influence of motivation, knowledge, and technological advances on investment decisions of UIN North Sumatra students in the Sharia capital market. the benefits of this research are as a means of increasing knowledge and insight about investment in the Islamic capital market and decision making in investing, adding to the treasury of knowledge as the development of research on the Islamic capital market, and a reference for research in formulating new problems and comparative materials for relevant research and can deepen knowledge in the field of Islamic capital markets. The type of research used is quantitative research with associative approach. The purpose of quantitative research is to test theories, find out the relationship between variables, establish facts, explain statistical descriptions, estimate and estimate the results. The population in this study was 170 students and the sample of this study was UIN North Sumatra students who invested in the Sharia capital market, with a total sample of 119 students. In this study, samples were selected using purposive sampling with Slovin formula and the data were analyzed using SPSS. The results of this study indicate that (1) the motivation variable has a significant and positive effect on investment decisions; (2) the knowledge variable has a significant and positive effect on investment decisions; (3) the technological progress variable has a positive and significant effect on investment decisions; (4) motivation, knowledge, and technological progress simultaneously affect investment decisions.